The skeletal maturity of Australian children aged 10-13 years in 2016 - Rachel L. Duckham; Nicola L. Hawley; Christine Rodda; Timo Rantalainen; Kylie D. Hesketh (Taylor & Francis Group, 2021)
Skeletal maturity can be used as a biological indicator of the tempo of growth in children and adolescents. We present a description of skeletal maturity from a cohort of white Australian children and describe variation in skeletal maturity based on child age. Participants (n = 71; age 10.5-13.9 years) were recruited from the 'Healthy, Active Preschool & Primary Years (HAPPY)' study. Left hand-wrist radiographs were used to determine skeletal maturity using the Tanner-Whitehouse III (TW3) RUS technique. In boys, the mean skeletal maturity offset (bone age - chronological age) was −0.12 ± 0.19 years and 57.9% had delayed skeletal maturity compared to chronological age. Among those with delayed skeletal maturity, the average delay was 0.99 years (range 0.02-2.54 years). In girls, skeletal age was advanced, on average, compared to chronological age by 0.32 ± 0.20 years. Among the 39.4% of girls with delayed skeletal maturity, the average delay was 0.48 years (range: 0.01-2.28). Four children in the sample exhibited a delay in skeletal maturity greater than 2 years. In the context of secular trends towards advanced skeletal maturity observed globally, delayed skeletal maturation in this white, economically privileged cohort are surprising and warrant further exploration.